2011
DOI: 10.1007/s12565-011-0109-7
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical review of the lateral collateral ligaments of the ankle: a cadaveric study

Abstract: Arrangements of the lateral collateral ligaments of the ankle are complex. Injuries to these ligaments can occur in the inverted planter flexed position of the ankle. Traditionally, the anterior talofibular ligament (ATFL) is the first ligament involved in such ankle injuries. We reviewed the anatomical arrangements of the lateral ankle. Twenty ankles from ten Caucasian cadavers were carefully dissected. Length and width of each ligament were measured in neutral, dorsiflexion and plantar flexion. The angle bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 8 publications
4
38
2
Order By: Relevance
“…Length decreased in dorsiflexion (18.81 mm) and eversion (18.25 mm) compared to neutral (20.17 mm) and increased in plantarflexion (21.06 mm) and inversion (20.26 mm). Raheem and O'Brien [22] reported similar changes in dorsiflexion (14.5 mm) and plantarflexion (18 mm) compared to neutral (15.5 mm). Nevertheless, both sets of results confirm that the ATFL is most taut in plantarflexion.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…Length decreased in dorsiflexion (18.81 mm) and eversion (18.25 mm) compared to neutral (20.17 mm) and increased in plantarflexion (21.06 mm) and inversion (20.26 mm). Raheem and O'Brien [22] reported similar changes in dorsiflexion (14.5 mm) and plantarflexion (18 mm) compared to neutral (15.5 mm). Nevertheless, both sets of results confirm that the ATFL is most taut in plantarflexion.…”
Section: Discussionmentioning
confidence: 85%
“…In the current study 22.9% of specimens had a single band, with two and three bands being observed in 56.3% and 20.8% of specimens respectively: this supports Milner and Soames [20] and Ugurlu et al [21], who both report the presence of one, two and three bands. Other authors [18,22,23] have reported one and two bands; however Sindel et al [25] found only two bands. Sarrafian (1993) [24] is of the opinion that the ATFL mainly consists of two bands, but it may occasionally have three.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations